Korupsi dalam Akuntansi Faktor Penyebab dan Solusi dalam Perspektif Etika Bisnis - Ahmad Raffi Arrasyid; Aulia Fitriani; Nur Zahra Masyidah; Sri Wahyu Ningsih; Miftahul Diva; Nurul Febriani; Kharisma Sianipar; Nurliza Lubis (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study aims to analyze the relationship between the ethics of the accounting profession and corruption cases, as well as how regulation and supervision can help reduce corrupt practices in the business and government sectors. This study uses a literature review method to analyze internal and external environmental factors that cause corruption in accounting, business ethics principles violated in corruption cases, and prevention efforts and the role of supervisory institutions in suppressing corrupt practices. The results show that corruption in accounting can be caused by internal and external environmental factors, such as a lack of internal supervision, a company culture that does not support ethics, and weak regulations. The principles of business ethics that are violated in corruption cases include the principles of integrity, objectivity, and transparency. Prevention efforts and the role of supervisory agencies can help reduce corrupt practices in accounting. This research is expected to contribute to the development of more ethical and transparent accounting theories and practices.